Additional mortality rate of wildfowl caused by ingestion of lead shotgun pellets: a re-analysis of data from a 70-year-old field experiment on wild Mallards Anas platyrhynchos - Green, Rhys E.; Pain, Deborah J. (Wildfowl, 2020)
A widely-used method for the estimation of numbers of deaths of wildfowl caused by the ingestion of spent lead gunshot pellets depends entirely upon field experiments on wild Mallards Anas platyrhynchos conducted 70 years ago in the USA by Frank C. Bellrose. The validity of this method has recently been questioned because of the simple method used to estimate the annual mortality caused by the experimental administration of lead gunshot and because the administration of shot appeared to increase the risk that treated birds would be shot by hunters, which might bias the mortality estimates. In this paper, we report a re-analysis of Bellrose’s data using a different method which removes the possible effect on mortality estimates of differences in the proportion of birds killed by hunters in the first year after release. Our results indicate that the additional mortality caused by the administration of lead gunshot in the first year after treatment was substantial and dependent upon the dose of gunshot administered, to a similar extent as was found by Bellrose.